RAHASIA AL-HAZFU DALAM GAYA BAHASA AL-QURAN - Suhaimi, Suhaimi (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2018)
One important theme in Arabic science is al-hazfu. This term in Indonesian is called Ellipsis. In our daily reality, there are often people who see that something that is not written or not mentioned in the text means that it is understood as something that does not exist and therefore is also not important. Though it is very possible that it has a very important meaning, even because it is very important, the Mutakallim (speaker) deliberately does not express it explicitly or explicitly with certain purposes. Such expression is one style of language which is considered by one linguist as one of the models of language beauty. Al-Quran as a divine greeting which has the beauty of a very high language is certainly not silent from the language style, meaning that the Qur'an also uses language style in the form of al-hazfu, where many lafaz that even though it is not mentioned, must be understood there, so that understanding of a verse will be more perfect. The style of language in the form of al-hazfu contains secrets that are very urgent to be revealed, so that various forms, places, causes and purposes or their benefits are clearly known. This very simple article is strived to uncover these things although it is also realized that what is described is not silent from various weaknesses and limitations.